Spatiotemporal variation of mammalian protein complex stoichiometries - Ori, Alessandro; Iskar, Murat; Buczak, Katarzyna; Kastritis, Panagiotis; Parca, Luca; Andrés-Pons, Amparo; Singer, Stephan; Bork, Peer; Beck, Martin (Genome biology, 2016)
Recent large-scale studies revealed cell-type specific proteomes. However, protein complexes, the basic functional modules of a cell, have been so far mostly considered as static entities with well-defined structures. The co-expression of their members has not been systematically charted at the protein level.